2022
DOI: 10.3389/fpubh.2022.843021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Physical Fitness Among Young Tennis Players: A Systematic Review

Abstract: BackgroundPhysical fitness comprises both health- and skill-related components that have been shown to correlate with the competitive ability of the athletes. Competitive ability of the athletes is strongly related to the positive or poor characteristics of physical fitness. Additionally, the adolescent stage is critical for the development of physical fitness. Physical fitness training for young tennis players should receive more attention. However, the current literature is deficient in in-depth reviews of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…The main databases search string is provided in Supplementary Appendix S1 . Furthermore, to find additional literature that might not have shown up in the search results using the four databases, a search was also carried out on Google Scholar and based on the reference lists of selected papers, previously relevant reviews and meta-analyses ( Singla et al, 2018 ; Sole et al, 2021 ; Colomar et al, 2022 ; Xiao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The main databases search string is provided in Supplementary Appendix S1 . Furthermore, to find additional literature that might not have shown up in the search results using the four databases, a search was also carried out on Google Scholar and based on the reference lists of selected papers, previously relevant reviews and meta-analyses ( Singla et al, 2018 ; Sole et al, 2021 ; Colomar et al, 2022 ; Xiao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Xio et al [ 35 ] presented results of the systematic review concerning the effects of exercise on physical fitness characteristics in young tennis players. The results of their review indicated that specific exercise training could significantly increase the physical fitness of young tennis players in terms of speed and agility, although there was a lack of evidence or conflicting evidence about strength and flexibility, as well as power, in this group.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, no hay estudios en pelotaris dirigidos a la mejora de la carga asociada al m/s mediante el entrenamiento de fuerza, por lo que resulta complicado comparar los datos con otros artículos y observar si los resultados obtenidos han sido los óptimos. Respecto a estudios similares en otros deportes que comparten factores de rendimiento como es el tenis, demuestran como programas de entrenamiento basados en la velocidad de ejecución muestran mejoras significativas en pruebas como el press banca, salto vertical y media sentadilla (Xiao et al, 2022).…”
Section: Discussionunclassified